Предмет: Алгебра,
автор: Катюшка061
помогите пожалуйста очень нужно
Приложения:
Ответы
Автор ответа:
0
1) cosx/sinx
2) sinx
3) sin^2(x)
4) (cos^2(x) - sin^2(x) - cos^2(x) - cosx*sinx)/(cosx+sinx) = - (sinx(cosx+sinx))/(cosx+sinx) = -sinx
2) sinx
3) sin^2(x)
4) (cos^2(x) - sin^2(x) - cos^2(x) - cosx*sinx)/(cosx+sinx) = - (sinx(cosx+sinx))/(cosx+sinx) = -sinx
Похожие вопросы
Предмет: Литература,
автор: vallivlad
Предмет: Математика,
автор: nuraniya975
Предмет: Биология,
автор: Dmitriy2021
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: anastaint